Does Auditor Objectivity Impact on the Relationship Between Information Technology and Efficiency and Effectiveness of Auditing: Evidence from Iraq - Salih, Waleed Khalid (Journal of Reviews on Global Economics, 2018)
This work aims to determine the effect of information technology on effectiveness and efficiency of auditors in the context of non-profit organizations in Iraq. Also to investigate the mediating influence on the relationship between information technology and the audit process’ effectiveness and efficiency. The study framework was based on those reported in literature pertaining to the unified theory of acceptance and use of technology (UTAUT). The target population in this work are auditors of Iraqi non-profit organizations. 354 questionnaires were sent to the participants, however, only 262 were returned and deemed applicable for this work, which culminates in a 74.3 percent response rate. SPSS (Statistical Package of Social Science) version 24 was utilized to examine the research model. The data were processed using many statistical techniques, such as (Descriptive Statistics, Correlations Analysis and Multiple Regressions). The study found that there is a significant influence on the auditors’ objectivity due to their role as a mediator on the relationship between IT and auditing non-profit organizations. The findings also confirmed that the auditors are required to upgrade their knowledge vis-Ã -vis computerized information systems to plan, direct, supervise, and review the performed tasks. The implications of these findings in this work are significant for managers and auditors, while also providing insights and encouraging evaluation of computerized accounting systems.